Intrinsic Promoter Activities of Primary DNA Sequences in the Human Genome - Sakakibara, Yuta (Oxford University Press, 2007)
In order to understand an overview of promoter activities intrinsic to primary DNA sequences in the human genome within a particular cell type, we carried out systematic quantitative luciferase assays of DNA fragments corresponding to putative promoters for 472 human genes which are expressed in HEK (human embryonic kidney epithelial) 293 cells. We observed the promoter activities of them were distributed in a bimodal manner; putative promoters belonging to the first group (with strong promoter activities) were designated as P1 and the latter (with weak promoter activities) as P2. The frequencies of the TATA-boxes, the CpG islands, and the overall G + C-contents were significantly different between these two populations, indicating there are two separate groups of promoters. Interestingly, similar analysis using 251 randomly isolated genomic DNA fragments showed that P2-type promoter occasionally occurs within the human genome. Furthermore, 35 DNA fragments corresponding to putative promoters of non-protein-coding transcripts (ncRNAs) shared similar features with the P2 in both promoter activities and sequence compositions. At least, a part of ncRNAs, which have been massively identified by full-length cDNA projects with no functional relevance inferred, may have originated from those sporadic promoter activities of primary DNA sequences inherent to the human genome.